-4y=6-5x

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Divide each term by -4 and simplify.

Divide each term in -4y=6-5x by -4.

-4y-4=6-4+-5x-4

Cancel the common factor of -4.

Cancel the common factor.

-4y-4=6-4+-5x-4

Divide y by 1.

y=6-4+-5x-4

y=6-4+-5x-4

Simplify 6-4+-5x-4.

Simplify each term.

Cancel the common factor of 6 and -4.

Factor 2 out of 6.

y=2(3)-4+-5x-4

Cancel the common factors.

Factor 2 out of -4.

y=2⋅32⋅-2+-5x-4

Cancel the common factor.

y=2⋅32⋅-2+-5x-4

Rewrite the expression.

y=3-2+-5x-4

y=3-2+-5x-4

y=3-2+-5x-4

Move the negative in front of the fraction.

y=-32+-5x-4

Dividing two negative values results in a positive value.

y=-32+5×4

y=-32+5×4

Reorder -32 and 5×4.

y=5×4-32

y=5×4-32

y=5×4-32

Rewrite in slope-intercept form.

y=54x-32

y=54x-32

Using the slope-intercept form, the slope is 54.

m=54

Find the Slope -4y=6-5x